ANALISIS PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PT XYZ - Marbun, Dedek Andri; Arista, Anggia (LPPM Universitas Putera Batam, 2023)
According to the relevant standards, the business undertakes workplace precautions for health and safety among its personnel. The aforementioned precautions are implemented to prevent employee incidents, and an approach for managing workplace security has been designed in accordance therewith PP. 50 Year 2012 on SMK3.to determine the percentage of staff members that miss time from work as a result of incidents that happen there, which can have an impact on output. Then the researcher uses the Lost Time Frequency Rate (LTFR) method.The purpose of this study was to determine the effect of work safety on work productivity, occupational health on work productivity and safety and health on work productivity in employees. The research method is quantitative, the research analysis uses the LFTR method and linear regression. The results show the calculation of the lost time ratio of workers who experience work accidents with the highest frequency is in 2018 which occurred a loss of working time of 31300.00 hours per million people working. There is an influence of occupational safety on work productivity in employees.